Geospatial approach for Landslides Vulnerability Assessment of Physical Infrastructures in Sireh Park, Johor Bahru - Jambo, Umar Mohammed; Mohd Faisal Abdul Khanan,; Zakaria Baharuddin,; Muhammad Zulkarnain Abdul Rahman,; Suzanna Noor Azmy,; Wan Hazli Wan Kadir, (Penerbit Universiti Kebangsaan Malaysia, 2023)
According to the landslide records between 1993 and 2019 in Malaysia, 171 individuals lost their lives, many others sustained injuries and numerous families evacuated. Additionally, infrastructures and vehicles incurred damage. Even though landslides present a risk to human life, environment, and infrastructures, there are few studies on landslides vulnerability in Malaysia with most of them focusing on social vulnerability neglecting the physical vulnerability. Consequently, a dearth of information on the vulnerability of an area to landslides may amplify the risks associated with landslides, and the relevant authorities in both the landslide-prone and affected regions may not implement the appropriate mitigation measures. The aim of this study is to estimate vulnerability of elements at risk to landslide in the hazard’s affected area of Sireh Park. An indicator based method was used to calculate the relative vulnerability index for each of the elements at risk. In applying the method, experts assigned weights to the indicators and their respective sub indicators based on their significance to landslides vulnerability. The indicators were grouped into clusters, the total values of weights for all the clusters equals to 1. The results of the study showed that about 252 elements at risk are exposed to landslides in Sireh Park, out of which 226 (89.7%) are buildings, while 26 (10.3%) are roads. The general level of buildings' vulnerability to landslides in the study area is relatively low, however about 20.4% of the buildings display a high degree of vulnerability. Meanwhile, the general vulnerability of roads sections to landslides is averagely high, with about 54.8% of the roads sections exhibiting a high degree of vulnerability while 16.1% exhibits low degree of vulnerability. The study can help stakeholders to identify locations with high landslide vulnerability and guide the development of mitigation measures and emergency preparedness plans to reduce the potential impact of landslides in the study area.